(untitled) (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Recently many laboratories are evaluating the usefulness of determining p53, and Ki67 proliferation activities using immunohistochemical techniques in cancer. Although the available studies suggest that these factors might help make treatment decisions in cancer patients, their clinical usefulness is still controversial. The present study was undertaken to see the expression of p53 and Ki-67 in breast carcinoma and their associations with histopathological variables. Methods: This cross-sectional analytical study was conducted in the Department of Pathology, in collaboration with the Department of Surgery, Rajshahi Medical College Hospital and the Department of Pathology, Bangobandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of one and a half year from July 2018 to December 2019. Resected specimens of breast tissue, histopathologically confirmed as breast carcinoma, were the study population. Histological grading of breast carcinoma was done according to Nottingham modification of the Bloom-Richardson system, while staging was done using Tumor-Node-Metastasis (TNM) classification of malignant tumors, as recommended by the Union for International Cancer Control (UICC). The Ki67 and p53 expressions were assessed by immunohistochemistry. Based on the Ki67 labeling index (Ki67-LI), the patients were divided into two groups – Ki 67 > 30% (considered as over-expressed) and ≤ 30% (considered as less expressed). Likewise, p53 immuno-expression was grouped as over-expressed (score ≤ 8) and low-expressed (score > 8). The histological grade, type, and stage were then compared between patients with tumours of high and low proliferating activities to find the associations of Ki67 and p53 with tumor grade, type, and stage. Result: In the present study, almost three-quarters (74%) of the specimen of the breast had high Ki67-LI and 26% intermediate and low Ki67-LI. The p53 was found to be highly expressed in the majority (86%) of the cases. Analyses of the association of biomarkers with histological grade, stage, and type revealed that advanced-stage breast cancers (Stage-IIIA) were more likely to be associated with high Ki67-LI than the early-stage breast cancers (Stage-IIA and Stage-IIB) (p = 0.023). Poorly differentiated (G3) carcinoma also more often tends to be associated with high Ki67-LI than with low and intermediate Ki67-LI (p = 0.066). Likewise, stage IIIA tumors and poorly differentiated carcinoma were also considerably higher in the p53 over-expressed group (23.3%) than in the low p53 expression group (14.3%) (p = 0.023). Conclusion: The study concluded that a substantial proportion of breast carcinomas demonstrates high Ki67-LI. The p53 overexpression is also found in the majority (86%) of the breast carcinoma cases. Both Ki67 and p53 proliferation activities show their significant presence in high-grade and advanced-stage tumours. Ibrahim Card Med J 2023; 13 (1&2): 11-18